2015
DOI: 10.5751/es-07686-200240
|View full text |Cite
|
Sign up to set email alerts
|

Local seafood: rethinking the direct marketing paradigm

Abstract: ABSTRACT. Faced with strict regulations, rising operational costs, depleted stocks, and competition from less expensive foreign imports, many fishers are pursuing new ways to market and sell their catch. Direct marketing arrangements can increase the ex-vessel value of seafood and profitability of operations for fishers by circumventing dominant wholesale chains of custody and capturing the premium that customers are willing to pay for local seafood. Our analysis goes beyond a paradigm that understands direct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 66 publications
(72 reference statements)
0
38
0
Order By: Relevance
“…; Stoll et al . ). We found that consumers more commonly identified the social benefits of local seafood, but that differences existed among respondents.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Stoll et al . ). We found that consumers more commonly identified the social benefits of local seafood, but that differences existed among respondents.…”
Section: Discussionmentioning
confidence: 97%
“…; Stoll et al . ), it was not clear how consumers understood these benefits and how their perceptions influence their choices. Our results suggest that consumers are more attune to the social than to the environmental benefits of purchasing local seafood, with benefits to the economy identified most frequently (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…CSFs are based on the community supported agriculture model in which consumers pre-pay for shares of seafood. Fishers have started to turn towards CSFs as a way to earn higher ex-vessel prices for their catch and cultivate new relationships with their communities by bypassing or partnering with traditional distributors (Stoll et al, 2015). Through these arrangements consumers gain access to a wide range of species, including 'underutilized' ones with which they may be unfamiliar, such as dogfish and herring.…”
Section: Discussion: Expanding the Geography Of Resilience In Fisheriesmentioning
confidence: 99%
“…They act as a type of "institutional starter" [54] by fostering the emergence of nascent institutions that facilitate the production and mobilization of social capital toward improved social, economic, and ecological conditions. Viewed through this lens, communities have to focus projects on actions that create a set of conditions that facilitate institutional emergence, such as social networks, rules, and norms, and help to sustain communities such that they may be responsive and resilient to disturbances that threaten the viability of the systems within which they operate.…”
Section: Discussionmentioning
confidence: 99%
“…Elements from the case study support the identification of the community as the appropriate territorial dimension of a socio-technical niche [61] to practice and experiment with such system/structural changes, alternative and more diverse supply chain structures, and new institutional governance and market arrangements. These identify and promote new relationships between actors [54,61]. The analysis suggests consideration of place in a holistic perspective, considering all the interrelationships among the different components.…”
Section: Discussionmentioning
confidence: 99%